Improvements of Ease of Doing Business and the Access to Justice in United Arab Emirates - Heikal, Sherif (Archives of Business Research, 2023)
There is an enormous body of legal literature hypothesizing that differences in economic prosperity can be traced to the legal systems of countries, in the same vein, some research has posited that countries with a sophisticated legal system have enjoyed greater per capita growth than countries whose legal systems having operational shortcomings. Hence, this Article provides an assessment on the role of the access to justice and the ease of ease of doing business in United Arab Emirates. This article finds that the access to justice in UAE have played a crucial role for not only the ease of starting the business but also provided a general healthy business environment.